Time-lapse analysis of potential cellular responsiveness to Johrei, a Japanese healing technique - Moore Dan; Taft Ryan; Yount Garret (BMC, 2005)
Abstract Background Johrei is an alternative healing practice which involves the channeling of a purported universal healing energy to influence the health of another person. Despite little evidence to support the efficacy of such practices the use of such treatments is on the rise. Methods We assessed cultured human cancer cells for potential responsiveness to Johrei treatment from a short distance. Johrei treatment was delivered by practitioners who participated in teams of two, alternating every half hour for a total of four hours of treatment. The practitioners followed a defined set of mental procedures to minimize variability in mental states between experiments. An environmental chamber maintained optimal growth conditions for cells throughout the experiments. Computerized time-lapse microscopy allowed documentation of cancer cell proliferation and cell death before, during and after Johrei treatments. Results Comparing eight control experiments with eight Johrei intervention experiments, we found no evidence of a reproducible cellular response to Johrei treatment. Conclusion Cell death and proliferation rates of cultured human cancer cells do not appear responsive to Johrei treatment from a short distance.